Bridging the Gap for Recent Immigrants in Canada: Exploring the Role of Community-Based Adult Education - Shibao Guo (Adult Education Research Conference, 2010)
This study investigates the role of community-based adult education in assisting immigrants with their settlement and adaptation in Canada. The study reveals that ethnic community organizations can play an important role in bridging the gap and providing accessible community-based adult education and professional services for recent immigrants and refugees to Canada.